Physicochemical origin of improvement of magnetic and transport properties of STT-MRAM cells using tungsten on FeCoB storage layer - Chatterjee, Jyotirmoy; Gautier, Eric; Veillerot, Marc; Sousa, Ricardo C.; Auffret, Stéphane; Dieny, Bernard (Applied physics letters, 2019)
We investigated and compared the structural and magnetic properties of MgO/FeCoB based out-of-plane magnetized tunnel junctions at the thin film level and the magneto-transport properties of the corresponding patterned spin transfer torque magnetic random access memory(STT-MRAM) cells comprising either Ta1 nm or W2/Ta1 nm cap layers for different annealing temperatures up to 455 °C. The W material in the cap was found to improve the structural stiffness of the perpendicular magnetic tunnel junctions (pMTJs) and most importantly prohibits Fe diffusion from the FeCoB storage layer to the cap layer, remarkably improving the thermal robustness and magneto-transport properties of the stacks and of the corresponding patterned memory cells. As a result, the interfacial anisotropy constant of the MgO/FeCoB interfaces is improved by 17%–29% compared to the Ta cap. The STT-MRAM cells fabricated from the pMTJ stacks with the W/Ta cap reveal a significant improvement of the tunneling magnetoresistance and thermal stability factor, which are 120% and 52 as compared to 70% and 35 for the stack with the Ta cap, respectively. This improvement is ascribed to the enhancement of MgO crystallinity upon higher temperature annealing (425 °C) and prohibition of Fe out-diffusion.